AI CHATBOTS IN ELT: EVALUATING THE IMPACT ON SPEAKING SKILL DEVELOPMENT OF HIGHER EDUCATION STUDENTS - Ravshanova Marjona Jumaniyoz qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article discusses the Effectiveness of AI-Powered Chatbots in Developing Speaking Skills of Higher Education Students.This study  addresses the perennial challenge of limited speaking practice opportunities in conventional English Language  Teaching  settings.  AI-powered  conversational  agents  (chatbots)  have emerged as a promising solution, offering students continuous, personalized practice and  automated  feedback.  The  primary  aim  of  this  research  is  to  evaluate  the effectiveness of integrating AI-chatbots into the English language teaching curriculum for  developing  the  speaking  skills  of  students  in  higher  education  institutions  in Uzbekistan.  A  12-week  quasi-experimental  study  was  conducted  involving  two groups: a control group (traditional instruction) and an experimental group (traditional instruction plus regular AI-chatbot practice). The students’ speaking performance was assessed  using  pre-tests  and  post-tests  focusing  on  fluency,  accuracy,  and  lexical richness. The findings indicate that the experimental group demonstrated a statistically significant improvement in speaking skills compared to the control group. Specifically, the  use  of  AI-chatbots  positively  enhanced  students’  fluency  and  motivation  for autonomous learning. The study confirms the pedagogical value of AI-chatbots as an effective  tool  for  teaching  English  in  the  Uzbek  educational  context  and  provides practical  implications  for  enhancing  English  language  teaching  programs  through technology integration.